1989
DOI: 10.1007/bf00381463
|View full text |Cite
|
Sign up to set email alerts
|

The role of short-term visuo-spatial memory in control of rapid multi-joint prehensive movements

Abstract: How memorized visuo-spatial information influences motor control and whether this information is able to replace the feedback processing in cases of visual deprivation was studied using an unrestrained finger- and hand-movement paradigm. Nineteen right-handed subjects were asked to grasp and lift a small block with the index finger and thumb of the right hand, as quickly as possible. The efficiency of motor performance was analysed by measuring the grasping time derived from tangential velocity profiles of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…WM processes are also employed during grasping movements, for example, to keep the goal relevant information for a subsequent execution of the grasp (e.g., Fiehler et al, 2011 ; Fournier et al, 2014 ). Accordingly, the execution of the grasping movements after a delay has been shown to depend on WM (e.g., Kohler et al, 1989 ; Binsted et al, 2006 ; Singhal et al, 2007 ; Hesse and Franz, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…WM processes are also employed during grasping movements, for example, to keep the goal relevant information for a subsequent execution of the grasp (e.g., Fiehler et al, 2011 ; Fournier et al, 2014 ). Accordingly, the execution of the grasping movements after a delay has been shown to depend on WM (e.g., Kohler et al, 1989 ; Binsted et al, 2006 ; Singhal et al, 2007 ; Hesse and Franz, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that vision is particularly important for the final adjustment during the terminal stages of the movement (8). Absence of vision during the pointing movement requires temporary remembering of target position in space (9). In addition, information about hand position during the pointing movement can be derived only from nonvisual inputs (10,ll).…”
mentioning
confidence: 99%
“…The link between the context updating, particularly the updating of WM with new stimulus–response pair, and movement re-planning also conforms to the motor control research suggesting the functional role of WM in manual action control. For example, WM stores the task-related target information for the upcoming movement (e.g., Hesse & Franz, 2009 , 2010 ; Hesse et al, 2016 ; Kohler et al, 1989 ; for a review, see Schenk & Hesse, 2018 ). Importantly, WM selects and prepares the movement plans, and changes them favoring the alternative new plans when necessary (e.g., Fournier et al, 2014 ; Gallivan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, movement re-planning–WM interactions during grasping movements are also compatible with the motor control research suggesting the functional role of WM in manual actions. For example, it has been shown that WM selects, prepares and changes the movement plans (e.g., Fournier et al, 2014 ; Gallivan et al, 2016 ) as well as keeps the task-related target information active for the upcoming movement (e.g., Hesse & Franz, 2009 , 2010 ; Hesse et al, 2016 ; Kohler et al, 1989 ; for a review, see Schenk & Hesse, 2018 ).…”
Section: Introductionmentioning
confidence: 99%